FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA DEPRESI PADA LANSIA (LITERATURE REVIEW) - Nurul Hidayah; Rahmi Syarifatun Abidah; Rifaatul Laila Mahmudah (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2025)
Depression is caused by several factors, namely biological, psychosocial, family support, grief, loneliness, sadness, gender, age. Previous researchers found that many possible causes of depression include impaired brain function related to mood regulation, stressful life events, increasing age. The impact that is very urgent if the elderly experience prolonged depression is suicide. The purpose of this study is to explain the factors associated with the occurrence of depression in the elderly. In the database to search for Literature Review using the keyword ((Related Factor) AND Depression) AND Elderly). There were 107 selected articles and 6 articles were found which will then be analyzed using JBI Critical Appraisal tools. The database used was Google Scholar, Garuda, and Semantic Scholar, PubMed. The selection was taken by paying attention to PEOS, then the journals were analyzed one by one. There is a relationship between family support and depression in the elderly, there is a relationship between gender and depression in the elderly, there is a significant relationship between age and the incidence of depression in the elderly, there is a relationship between grief factors with the incidence of depression in the elderly, there is a relationship of social interaction with the incidence of depression in the elderly, there is a relationship between the sadness factor and the incidence of depression in the elderly. There is one factor associated with the occurrence of depression in the elderly, namely psychosocial factors. In this factor sad all the time is very influential factor on factors related to the occurrence of depression in the elderly. Researchers conclude that psychosocial factors are very influential on factors related to depression in the elderly, further researchers should focus on psychosocial factors because these factors are very influential on factors related to depression.